2018
DOI: 10.21276/aimdr.2018.4.4.en3
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Patients Attending ENT OPD at a Medical College in Western UP

Abstract: Background: ENT ailments are one of the most common causes for patients to attend hospitals. The present study was undertaken to assimilate data on patients visiting ENT OPD in consecutive 3 months, so that the trend of diseases in this part of Uttar Pradesh could be studied. Objective: To study the epidemiological profile of otorhinolaryngology disorders in the patients attending ENT OPD, Muzaffarnagar Medical College. Methods: This was a retrospective record based study, done in department of ENT &HNS from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(7 reference statements)
2
0
0
Order By: Relevance
“…In this study attempted to find out the pattern of ENT diseases with which patients came to a referral centre in Dhaka city. The current study showed male 52.82% is more than that of female 47.17% and male: female ratio is 1.12:1 that correspond to the studies done elsewhere [9,21,27,30,33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study attempted to find out the pattern of ENT diseases with which patients came to a referral centre in Dhaka city. The current study showed male 52.82% is more than that of female 47.17% and male: female ratio is 1.12:1 that correspond to the studies done elsewhere [9,21,27,30,33].…”
Section: Discussionsupporting
confidence: 92%
“…Total number of patients came with problem in the throat is 19.61% (723) which correlates with other studies [9,27]. Laryngeal carcinoma accounted for 0.84% (25), Hypopharyngeal carcinoma 0.19% and benign laryngeal lesions 0.45% found in our study, similar report found in other studies [25][26][27]33].…”
Section: Discussionsupporting
confidence: 91%